Interpolation polynomials via AIFS - Kocić, Ljubisa; Gegovska-Zajkova, Sonja; Andova, Vesna (My University, 2009)
The general theory of IFS - AIFS relations is applied to the case of polynomial attractors. The starting point is B´ezier subdivision embodied in two linear contractions of Rn space.